The association between objective cognitive measures and ecological-functional outcomes in COVID-19 - Ottonello, Marcella; Fiabane, Elena; Aiello, Edoardo Nicolò; Manera, Marina Rita; Spada, Francesca; Pistarini, Caterina (Frontiers in Psychology, 2022)
, may follow SARS-CoV-2 infection. However, the ecological-functional relevance of such objective deficits is currently under-investigated. This study thus aimed at investigating the association between objective cognitive measures and both physical and cognitive, ecological-functional outcomes in post-COVID-19. Methods. Forty-two COVID-19-recovered individuals were administered the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). The Functional Independence Measure (FIM) was adopted to assess functional-ecological, motor/physical (FIM-Motor) and cognitive (FIM-Cognitive) outcomes at admission (T0) and discharge (T1). Results. When predicting both T0/T1 FIM-total and -Motor scores based on MMSE/MoCA scores, premorbid risk for cognitive decline (RCD) and disease-related features, no model yielded a significant fit. However, the MoCA - but not the MMSE significantly predicted T0/T1 FIM-Cognitive scores. The MoCA was significantly related only to T0/T1 FIM-Cognitive Memory items. Discussion. Cognitive measures are not associated with physical/motor everyday-life outcomes in post-COVID-19 patients. The MoCA may provide an ecological estimate of cognitive functioning in this population.